PENGARUH KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL, DEWAN KOMISARIS INDEPENDEN DAN KOMITE AUDIT TERHADAP TAX AVOIDANCE DENGAN SIZE PERUSAHAAN SEBAGAI VARIABEL MODERASI - Samino Hendrianto (Universitas Muhammadiyah Tangerang, 2022)
The purpose of this study was to determine the effect of institutional ownership, managerial ownership, independent commissioners, and audit committees on tax avoidance with Size Perusahaan as a moderating variable in food and beverage sector companies listed on the Indonesia Stock Exchange (IDX). The research time period used is 5 years, namely the 2017-2021 period. The sampling technique used purposive sampling technique. Based on the predetermined criteria, 17 companies were obtained. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analytical method used is panel data regression analysis. The results show that institutional ownership has a negative effect on tax avoidance, managerial ownership has a positive effect on tax avoidance and the independent board of commissioners has a negative effect on tax avoidance. The audit committee has no effect on tax avoidance, and institutional ownership, managerial ownership, independent commissioners, and audit committees. jointly affect tax avoidance.Tax Avoidance, Institutional Ownership, Managerial Ownership, Independent Board Of Commissioners, Audit Committee